Analisis Model Peningkatan Hidup Islami Melalui Prinsip Good Corporate Governance : Telaah Al-Qur’an Dan Al-Hadist - Anjani, Ainaya; Ningsih, Yuliati; Djasuli, Mohamad (CV. ITTC INDONESIA, 2022)
This study aims to analyze how to apply the concept of good corporate governance (GCG) as a model in improving Islamic life. The majority of the population in Indonesia are Muslims, of course they must know and also understand the Islamic principles of good corporate governance in doing business. The method used in this study is a descriptive qualitative method, which focuses on the author's understanding, thoughts, and perceptions about the application of the principles of Islamic good corporate governance using Al-Qur'an and Hadith studies